2019
DOI: 10.1007/s10035-019-0879-5
|View full text |Cite
|
Sign up to set email alerts
|

Modelling particle kinetic behaviour considering asperity contact: formulation and DEM simulations

Abstract: Self-archiving for articles in subscription-based journals Springer journals' policy on preprint sharing. By signing the Copyright Transfer Statement you still retain substantial rights, such as self-archiving: Author(s) are permitted to self-archive a pre-print and an author's accepted manuscript version of their Article. ………. b. An Author's Accepted Manuscript (AAM) is the version accepted for publication in a journal following peer review but prior to copyediting and typesetting that can be made available u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…It has been shown that numerical discrete element method (DEM) 3 simulations that use idealized circular or spherical particles cannot quantitatively reproduce the mechanical behavior of natural sand, often underrepresenting the shear strength 4 . Particle shape is a general concept that incorporates both intermediate scale measures including sphericity and roundness and small scale measures such as surface asperities 1,5,6 . Here, surface asperities refer to the unevenness, roughness, or ruggedness of the particle surface, which is inevitable for even apparently regular shaped particles, visible in Figure 1A–C.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that numerical discrete element method (DEM) 3 simulations that use idealized circular or spherical particles cannot quantitatively reproduce the mechanical behavior of natural sand, often underrepresenting the shear strength 4 . Particle shape is a general concept that incorporates both intermediate scale measures including sphericity and roundness and small scale measures such as surface asperities 1,5,6 . Here, surface asperities refer to the unevenness, roughness, or ruggedness of the particle surface, which is inevitable for even apparently regular shaped particles, visible in Figure 1A–C.…”
Section: Introductionmentioning
confidence: 99%
“…Collisions are extensively treated in the mechanics literature dealing with fluid mechanics, [1][2][3][4][5][6] granular matter, [7][8][9] and aerosol science, 10,11 among other fields. Much of this research is focused on the impact of spheres on surfaces [12][13][14][15][16][17] and two-sphere collisions.…”
Section: Introductionmentioning
confidence: 99%
“…Q[ 'pNrND C@Uv l} QO xWwoOQo |=yxvwtv R= V}@ OYQO 48 w l=m]Y= R= |}xv=O |=yl=N QO Ctw=kt = Q} R "CU= xOw@ u}at |x@v=Hxty Q=Wi O=H}= |wQmQ}e |=ypmW =@ C= QP u}@ |QDy@ CU@ w pik w xDiQo C -=Wv C= QP u}@ |wQ Q@ C= QP VRer R= w xOW |}xQP u}@ l=m]Y= V}=Ri= x@ QHvt xm CU= xOW =@ xvwtv Q=DN=U QO Q}}eD p}rOx@ xWwoR}D |xvwtv QO sHL Q}}eD "CU= xDU=m Qo}Om} "CU= xOw@ QDW}@ C= QP |}=Q;R=@ w Q=@ p=ta= QF= QO |=yQ=Wi w 0=78 w 0=66 '0=42 pNrND |=yC@Uv QO xWwoR}D x@ \w@Qt |=yQ=Owtv '=yu; j@=]t xm OwW|t xOy=Wt p=mU=Bwr}m 300 w 100 QO XNWt |xvwtv l} OvDUy j@]vt Qo}Om} Q@ , =@} QkD hrDNt |}=Q}t ? }=Q[ |=y|R=Ux}@W QO QwmPt |}=Q}t QF= w u}at |x@v=Hxty Q=Wi w pNrND C@Uv xDUy; |i=m |xR=Ov= x@ |Q=PoQ=@ CaQU = Q} R "CU}v xHwD p@=k |m}D=DU=x@W V}=tR; xm OwW pY=L u=v}t]= =D x}v=F Q@ QDt 3 10 6 CU= xOW ?=NDv= OwOL \ki w xOw@ |R=wt sy =@ , =@} QkD 'Ow@ hrDNt |x@v=Hxty Q=Wi wO x@ \w@Qt |x@v=Hxty Q=Wi x@ \w@Qt |SQv= K]U Ov=xDW=O Cw=iD Qo}Om} =@ p=mU=Bwr}m 60 |SQv= K]U 'xWwoR}D |=yxvwtv "CU= xOw@ QDq=@ p=mU=Bwr}m 60 '|r=mU=Bwr}m 300 ' [12] 2019 u= Q=mty w 11 nvw xm CU= |r=L QO u}= &OvDW=O |QDq=@ |xOWxQ}NP C@Uv V}=Ri= =@ "CU= QDW}@ |wQmQ}e C= QP =@ =yxvwtv QO xOW p}=R |SQv= xm OvOkDat 23 \UwDt Qw] x@ ? }DQD x@ |SQv= K]U 'xWwoR}D w xWwoOQo |=yxvwtv QO pNrND QO pNrND C@Uv =@ |SQv= K]U Vy=m MQv "CU= xOQm =O}B Vy=m OYQO 12 w xOW xQ}NP |SQv= 'u=Um} \}=QW QO "CU= xOw@ xWwoR}D R= V}@ xWwoOQo |=yxvwtv |SQv= QO |QF= |}=Q}t ?…”
mentioning
confidence: 99%
“…}=Q[ w xOw@ Q@=Q@ , =@} QkD hrDNt |}=Q}t ? }=Q[ =@ =yxvwtv QO [12] "=yxvwtv |}=Q}t ? }=Q[ w pNrND C@Uv |}=Q}t C@Uv "13 pmW |}=Q}t C@Uv |=yQ=Owtv "CU= xOw@ QDW}@ OYQO 1=5 OwOL p=mU=Bwr}m 100 Q}}eD 'p=mU=Bwr}m 300 x@ 100 R= x@v=Hxty VvD Q}}eD =@ xWwoR}D |=yxvwtv |= Q@ "Ov=xDW=Ov |UwULt xm |Qw]x@ &CU= xOW |}=Q}t C@Uv Vy=m x@ QHvt pNrND C@Uv V}=Ri= |=yxvwtv |}=Q}t C@Uv '0=42 w 0=66 x@ 0=78 R= pNrND C@Uv Vy=m =@ OYQO 2 w 3 ?…”
mentioning
confidence: 99%
See 1 more Smart Citation